Minimizing Work Zone Mobility Impacts using Project Coordination. Issue 2 (February 2019) - Theiss, LuAnn; Ullman, Gerald L.
Under the Every Day Counts program, the Federal Highway Administration has been promoting technologies and practices that can shorten the project delivery process, enhance durability and safety, reduce congestion, and improve environmental sustainability. The focus is on providing efficiency through technology and collaboration. This includes strategies for Project Coordination (PC) which can be applied to a single project, or more commonly, among multiple projects within a corridor, network, or region, and possibly across agency jurisdictions, to minimize work zone impacts and produce time and cost savings. The purpose of this document is to provide guidance on implementing PC in the planning, design, and delivery phases of projects. It summarizes key steps for successfully implementing PC, using a systematic approach to meet a specific set of clearly defined objectives. The steps include: establishing the PC vision; developing details of how PC will occur; educating and informing personnel and stakeholders; implementing the PC process; and refining the process. A case study of PC in Texas is included to demonstrate successful application of the approach.